Interpersonal Skills and Powerpoint Training to Improve Presentation Skills Among the First-Year Student at Islamic University - Safiruddin Al Baqi; Kharisul Wathoni (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
Presentation is an essential ability for every college student, including a student at Islamic University, because many agendas require this ability both in class and organization. This study aims to determine the effectiveness of interpersonal skills training and PowerPoint training to improve the presentation skills of first-year students. This study used an experimental design that is one group pretest-posttest design. The subjects of this study were 24 first-year students (6 male; 18 female). The students were divided into seven groups consisting of 3 to 4 students. The training was carried out in 4 sessions, namely listening skills, public speaking, use of power points, and practice of preparing presentations. Pre-test and post-test data were taken before and after training by assessing the presentation skills of each group. Pre-test and post-test data show an increase in the average from 65.43 to 86.29. Further analysis using paired sample t-tests showed a significance value of 0.00 (0.05), so it can be concluded that there were differences in students' abilities in presentation between before and after training. These results will be more representative of the research used a broader population, so it is recommended to further researchers to reach a broader community to achieve more representative results.Presentasi merupakan kemampuan penting yang harus dimiliki setiap mahasiswa termasuk mahasiswa di kampus Islam, karena banyak agenda yang menuntut akemampuan ini baik dikelas maupun organisasi. Penelitian ini bertujuan untuk mengetahui efektifitas pelatihan interpersonal skills dan pelatihan penggunaan power point untuk meningkatkan keterampilan presentasi mahasiswa baru. Penelitian ini menggunakan desain penelitian eksperimen yaitu one group pretest-posttest design. Subjek penelitian ini merupakan mahasiswa tahun pertama yang berjumlah 24 orang (6 laki-laki; 18 perempuan). Mahasiswa tersebut kemudian dibagi menjadi 7 kelompok yang terdiri dari 3 hingga 4 orang. Pelatihan dilakukan dalam 4 sesi yaitu tentang keterampilan menyimak, keterampilan public speaking, penggunaan power point, dan praktik menyiapkan presentasi. Data pre-test dan post-test diambil sebelum dan sesudah pelaksanaan pelatihan dengan meniai keamampuan presentasi masing-masing kelompok berdasarkan kemampuan public speaking dan penggunaan power point. Data pre-test dan post-test menunjukkan adanya peningkatan nilai rata-rata dari 65.43 menjadi 86.29. Analisis lebih lanjut menggunakan paired sample t-test menunjukkan nilai signifikansi sebesar 0.00 (0.05), sehingga dapat disimpulkan bahwa ada perbedaan kemampuan mahasiswa dalam presentasi antara sebelum dan sesudah pelatihan. Hasil ini akan lebih representatif jika penelitian dilakukan kapada populasi yang lebih luas, sehingga disarankan kepada peneliti selanjutnya untuk menjangkau populasi yang lebih luas untuk mencapai hasil yang lebih representatif